Executive Review and the Youngstown Categories: Vulnerability of Environmental Regulations to Unbounded Executive Review - Rarrick, Lee C. (Columbia Journal of Environmental Law, 2019)
[C]omprehensive and undefined presidential powers hold both practical advantages and grave dangers for the country . . . . -Justice Jackson The power of executive review remains imperfectly limited and defined—it therefore holds such potential dangers and advantages. By executive review I mean the power of the President to interpret the law and determine for himself whether a given law or provision is constitutional. Most commentators agree that this power exists legitimately in one form or another. But some argue that it is virtually unbounded, save for the president’s own sense of deference to the other branches and his self-interest to remain in office. Such a comprehensive power surely is as dangerous as that of which Justice Jackson warns in his concurrence in Youngstown Sheet & Tube Co. v. Sawyer, if not more so. Moreover, if fully utilized, executive review would leave the judiciary with no authority, save over itself. Unbounded executive review could also be used as a tool to undermine well-established legal doctrines which underpin entire fields of regulation, especially with respect to environmental law, as discussed herein. If left unchecked by any means with real bite, executive review has the potential to turn the Executive into a truly despotic branch. This Note endeavors to determine the ambit of the validity of executive review, as well as to find such a means to delimit the power of executive review, hopefully without simultaneously removing from it all practicality. Part II provides some of the classic arguments supporting the validity of executive review, as well as a few of my own inspired by the methods that Professor Akhil Amar advances in his book, America’s Unwritten Constitution: The Precedents and Principles We Live By. Part III outlines the different types of presidential action that rely on the power of executive review, and provides a framework for analyzing and scrutinizing the various uses and forms of executive review. While this Note does not systematically outline all of the arguments criticizing the validity of the power, to the extent that they attempt to refute the power altogether, they have been satisfactorily rebutted elsewhere. However, this Note builds upon some of those critiques in Part IV, in arguing for the limitation of executive review. Part IV first evaluates Professor Michael Stokes Paulsen’s arguments for essentially unbounded executive review. Next, it theoretically applies executive review in the environmental law context in order to highlight the need to limit the power, as it is perhaps the field most vulnerable to the potential abuses of executive review. Part IV then looks to recent judicial precedent as a possible foundation for limiting the power, and addresses some practical considerations relevant to any such limitation. Finally, Part V provides a brief conclusion.